Comparative Water Quality Analysis in Beso River in District Jaunpur, Azamgarh and Ghazipur Uttar Pradesh - Shireesh, Priydarshi; Kumar, Tiwari Atul; Prashant, Singh; Kumud, Rai; Brat, Mishra Dev (The Scientific Temper, 2021)
The Beso River originates from village Shahapur in District Jaunpur and enters in District Azamgarh after Jaigaha and finally merges into river Ganga in District Ghazipur Uttar Pradesh. It flows south-eastward for almost 95 km only through three districts of eastern Uttar Pradesh. The sample has been collected from three sites indicated by S. S1 from Lakhmapur Jaunpur, S2 from Lalganj Azamgarh, and S3 from Jakhania Ghazipur. The sample has been collected five times i.e. in May, August, November, January, and March on the second Sunday of the month in the year 2020-2021. During tabulation of data five reading from each sample have taken and bio statistically analyzed by students T-test for all parameters for all times and only significant data have been considered. The mean value for the pH as 7.4 Ammoniac Nitrogen as 66.0 ppm, Temperature as 28.660C, B.O.D 235.33 C.O.D 271, Free CO2 260 ppm TDS as 543.33ppm, Cu 2.47 ppm, Iron Total as 2.09 ppm Zinc 6.46 ppm, Cr 3.58ppm, Phenolic Compounds as 5.36 ppm and Conductivity as 373.73 μ S/cm. have been measured by implication of different techniques. During the investigation, only Cu and total Iron values are measured lower to normal while other parameters reported high to normal values. Overall all physiochemical data indicate the water quality tends to be increased polluted as river move to Sangam from Ganga. Yet the water quality of Beso is many times better than River Sai and Gomati